Carbonatação acelerada de concretos com cinza de casca de arroz sem moagem - Mazza, Roger (2015)
The carbonation is a physicochemical phenomenon that occurs naturally in concrete structures. The greater the presence of carbon dioxide (CO₂) in the atmosphere and in contact with moisture and hydration products of cement, the greater the depth of carbonation. Its main effect by reducing the alkalinity (pH) is the armature depassivation, which leaves the steel unprotected and susceptible to corrosion. In view of this, the present study aimed to verify the technical viability of using unground rice husk ash (natural NRHA) in partial replacement of cement for concrete for structural purposes against accelerated carbonation, as well as to collaborate with sustainable development in construction, since NRHA are residues from industrial processes of grain processing, which often are discarded directly into the environment without any environmental concern. Based on these principles, the mixtures were investigated CPII-Z and CP-IV with contents of 15% of cement mass replacement by NRHA and GRHA for w/b ratios of 0.45, 0.55 and 0.65 and compared with the REF mixtures. The depths were verified, the carbonation coefficients and the calcium hydroxide contents remaining after 91 days. Accelerated carbonation tests were performed at 4, 8, 12 and 16 weeks of exposure to CO₂ in an environmental chamber as the recommendation of RILEM TC 116-PCD (1999). The results showed that the carbonation depths were increased over time and the w/b ratios stipulated in this study for all mixtures, yielding the lowest depths to the lowest w/b of REF and CPII-Z mixtures. For NRHA mixtures, predominated shallower depths for both cements (CPII-Z and CP-IV) when compared with GRHA, yielding lower depths for CPII-Z than for CP-IV. When compared on an equal w/b ratio and resistance, was observed that carbonation coefficients depended on the type of cement and on the RHA of each mixture. The lowest coefficients were obtained for REF and CPII-Z mixtures, as well the highest contents of calcium hydroxide (CH) when compared to the contents of CP-IV. For mixtures containing RHA additions, predominated better results for NRHA mixtures compared with GRHA, verifying for mixtures of NRHA of CPII-Z and CP-IV for resistance C30 it is possible to use in concrete for structural purposes when the variable to be considered is the carbonation.